CHD7 Regulates Osteogenic Differentiation of Human Dental Follicle Cells via PTH1R Signaling - Caojie Liu; Qiwen Li; Qingyue Xiao; Ping Gong; Ning Kang (Stem Cells International)
Chromodomain helicase DNA-binding protein 7 (CHD7) is an ATP-dependent chromatin remodeling enzyme, functioning as chromatin reader to conduct epigenetic modification. Its effect on osteogenic differentiation of human dental follicle cells (hDFCs) remains unclear. Here, we show the CHD7 expression increases with osteogenic differentiation. The knockdown of CHD7 impairs the osteogenic ability of hDFCs, characterized by reduced alkaline phosphatase activity and mineralization, and the decreased expression of osteogenesis-related genes. Conversely, the CHD7 overexpression enhances the osteogenic differentiation of hDFCs. Mechanically, RNA-seq analyses revealed the downregulated enrichment of PTH (parathyroid hormone)/PTH1R (parathyroid hormone receptor-1) signaling pathway after CHD7 knockdown. We found the expression of PTH1R positively correlates with CHD7. Importantly, the overexpression of PTH1R in CHD7-knockdown hDFCs partially rescued the impaired osteogenic differentiation. Our research demonstrates that CHD7 regulates the osteogenic differentiation of hDFCs by regulating the transcription of PTH1R.